2012
DOI: 10.3390/ijms13033176
|View full text |Cite
|
Sign up to set email alerts
|

Arabidopsis Serine Decarboxylase Mutants Implicate the Roles of Ethanolamine in Plant Growth and Development

Abstract: Abstract:Ethanolamine is important for synthesis of choline, phosphatidylethanolamine (PE) and phosphatidylcholine (PC) in plants. The latter two phospholipids are the major phospholipids in eukaryotic membranes. In plants, ethanolamine is mainly synthesized directly from serine by serine decarboxylase. Serine decarboxylase is unique to plants and was previously shown to have highly specific activity to L-serine. While serine decarboxylase was biochemically characterized, its functions and importance in plants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
34
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 29 publications
3
34
0
Order By: Relevance
“…Additionally, these sugars might prevent cellular dehydration by deep insertion between lipid layers (Van den Ende, 2013). Ethanolamine is a known precursor of phosphatidylethanolamine and phosphatidylcholine, both major phospholipids in eukaryotic membranes (Kwon et al, 2012). Membrane properties and composition directly affect their permeability to solutes, water, and protons, potentially affecting protein membrane activities (Burgos et al, 2011).…”
Section: Mesophyll Conductance and Primary Metabolism: A Complex Intementioning
confidence: 99%
“…Additionally, these sugars might prevent cellular dehydration by deep insertion between lipid layers (Van den Ende, 2013). Ethanolamine is a known precursor of phosphatidylethanolamine and phosphatidylcholine, both major phospholipids in eukaryotic membranes (Kwon et al, 2012). Membrane properties and composition directly affect their permeability to solutes, water, and protons, potentially affecting protein membrane activities (Burgos et al, 2011).…”
Section: Mesophyll Conductance and Primary Metabolism: A Complex Intementioning
confidence: 99%
“…The embryo lethality of cek4-1/+ may be due to a deficiency in phospholipid biosynthesis because mutation in PECT, which catalyzes the reaction following CEK, affects PtdEtn biosynthesis and results in an embryo-lethal phenotype (Mizoi et al, 2006). Moreover, a null mutation in SDC may be lethal (Kwon et al, 2012). Furthermore, mutation in the gene encoding lysophosphatidic acid acyltransferase1 (LPAAT1/ATS2), a key enzyme in de novo glycerolipid biosynthesis (Kennedy pathway), results in an embryo-lethal phenotype (Kim and Huang, 2004;Yu et al, 2004).…”
Section: Role Of Cek4 In Embryo Developmentmentioning
confidence: 99%
“…In addition, knocking out of PMT1 (or PEAMT1, XPL1) reduces PtdCho levels slightly (CruzRamírez et al, 2004). Furthermore, a leaky mutant of SDC showed a severe growth defect, which suggests that SDC knockout is lethal (Kwon et al, 2012). Therefore, P-Etn synthesis may be crucial for the biosynthesis of PtdCho and PtdEtn.…”
Section: Introductionmentioning
confidence: 99%
“…LKE15-induced chlorophyll and phosphoserine production could be used to increase the serine content of oriental melon plants. The decarboxylation of serine produces ethanolamine, which is involved in several physiological process including inflorescence development, floral fertility, and flowering (Kwon et al 2012). Hao et al (2004) reported that the external application of a cysteine-derived amino acid, taurine, increased wheat seedling growth.…”
Section: Effect Of Bacillus Sp Lke15 Culture Filtrate On Host Plant mentioning
confidence: 99%